STAGES OF SECOND LANGUAGE ACQUISITION IN CHILDREN (Modern education and development, 2025)
In today’s increasingly globalized world, learning a second language has become more than just an academic skill—it is a gateway to broader communication and cultural understanding. Children, in particular, have a natural ability to acquire languages more quickly and intuitively than adults. However, second language acquisition in children follows several unique stages, each with its own characteristics and challenges. This article explores the stages of second language acquisition in children, highlighting the key features of each phase, the obstacles learners may encounter, and effective teaching strategies to support their language development.